Morfogeometría del caparazón del cangrejo Damithrax spinosissimus (Decapoda: Mithracidae) en tres islas del Caribe suroccidental - Martínez-Campos, Bibian (Universidad de Costa Rica, 2016)
Morphogeometric variation in the caparace of “king crab” Damithrax spinosissimus” (Decapoda: Majidae) over three islands in the southwestern Caribbean. The Caribbean king crab Damithrax spinosissimus is a potential fishery resource biologically little known and considered as a vulnerable species in some regions. The mosaic distribution and the great environmental heterogeneity due the oceanographic, landscape and ecological features in the Caribbean may stimulate the phenotypic variability of D. spinosissimus among sites. To evaluate differences in crab carapace size and shape among islands and between sexes, it was used the Geometric Morphometrics based on landmarks and univariate and multivariate statistical analysis. The results indicate strong sexual dimorphism in carapace size and shape. Similarly, this work provided evidence of differences in caparace size and shape among islands that may explained by two non-excluding alternatives: genetic differences and phenotypic plasticity in response to environmental heterogeneity of the sector. This study is a contribution to the knowledge of D. spinosissimus biology and indicates that the management strategies for the species must be different for each island.